Automaticity: schema modes in addiction - Boog, Michiel; Tibboel, Helen (Frontiers in Psychiatry, 2023)
Automaticity is a hallmark of substance use disorder. In Schema Therapy (an evidence-based form of psychotherapy, that has also been applied to substance use disorders), automaticity appears to be a relevant variable. However, the role of automaticity in Schema Therapy has never been made explicit. In the present article, we investigate the role of automaticity in schema modes and its role in different phases in Schema Therapy for substance use disorders. In performing this investigation, we facilitate a better understanding of the working mechanisms of Schema Therapy, and, vice versa, suggest an alternative understanding of automaticity in substance use disorders. We suggest that the automatic use of substances is way of coping with schemas and, therefore, is the consequence of schema mode activity. In the article, four characteristics of automaticity (unconscious, uncontrollable/uncontrolled, efficient, fast) are translated to schema modes. Subsequently, a Schema Therapy case of a patient suffering from an alcohol use disorder and a narcissistic personality disorder is discussed, focusing on the four facets of automaticity. Last, implications for theory, clinical practice and future research are discussed.